Availability, accessibility, and use of green spaces and cognitive development in primary school children - Fernandes, Amanda; Krog, Norun Hjertager; McEachan, Rosemary; Nieuwenhuijsen, Mark; Julvez, Jordi; Márquez, Sandra; de Castro, Montserrat; Urquiza, José; Heude, Barbara; Vafeiadi, Marina; Gražulevičienė, Regina; Slama, Rémy; et al. (Environmental pollution (1987), 2023)
Green spaces may have beneficial impacts on children's cognition. However, few studies explored the exposure to green spaces beyond residential areas, and their availability, accessibility and uses at the same time. The aim of the present study was to describe patterns of availability, accessibility, and uses of green spaces among primary school children and to explore how these exposure dimensions are associated with cognitive development. Exposures to green space near home, school, commuting route, and other daily activity locations were assessed for 1607 children aged 6–11 years from six birth cohorts across Europe, and included variables related to: availability (NDVI buffers: 100, 300, 500 m), potential accessibility (proximity to a major green space: linear distance; within 300 m), and use (play time in green spaces: hours/year), and the number of visits to green spaces (times/previous week). Cognition measured as fluid intelligence, inattention, and working memory was assessed by computerized tests. We performed multiple linear regression analyses on pooled and imputed data adjusted for individual and area-level confounders. Availability, accessibility, and uses of green spaces showed a social gradient that was unfavorable in more vulnerable socioeconomic groups. NDVI was associated with more playing time in green spaces, but proximity to a major green space was not. Associations between green space exposures and cognitive function outcomes were not statistically significant in our overall study population. Stratification by socioeconomic variables showed that living within 300 m of a major green space was associated with improved working memory only in children in less deprived residential areas (β = 0.30, CI: 0.09,0.51), and that more time playing in green spaces was associated with better working memory only in children of highly educated mothers (β per IQR increase in hour/year = 0.10; 95% CI: 0.01, 0.19). However, studying within 300 m of a major green space increased inattention scores in children in more deprived areas (β = 15.45, 95% CI: 3.50, 27.40). [Display omitted] •Green space availability, accessibility and use are unequal across socioeconomic groups.•Availability more than accessibility seems to foster play time in green spaces.•Accessibility improved working memory in children of higher socioeconomic areas.•Play time in green spaces improved working memory in children of higher educated mothers.•Accessibility increased inattention in children studying in more deprived areas.